Robson Classification System Applied to Induction of Labor - Sara Vargas; Susana Rego; Nuno Clode (Revista Brasileira de Ginecologia e Obstetrícia, 2018)
Abstract Objective Induction of labor (IL) is a common obstetric procedure, but it is questionable whether or not it results in higher cesarean section (CS) rates. The present study aims to evaluate the impact of IL in the overall CS rates and to analyze these rates according to the method of IL employed and to the Robson group in which it was applied. Methods We have conducted a retrospective study including pregnant women whose labor was induced at a tertiary hospital in 2015 and 2016. All women were classified according to the Robson Classification System (RCS). The CS rates were analyzed and compared regarding the method of IL employed. Results A total of 1,166 cases were included. The CS rate after IL was 20.9%, which represented 23.1% of the total of CSs performed in 2015 and 2016. The highest CS rates were recorded in RCS groups 5 (65.2%) and 8 (32.3%). Group 2 was the highest contributor to the overall CS rate, since it represented 56.7% of the population. The intravaginal prostaglandins method was the most used (77%). Transcervical Foley catheter was the preferredmethod in group 5 and intravaginal prostaglandins in all the other groups. The CS rate was higher when transcervical Foley catheter was used (34.1%). Conclusion Transcervical Foley catheter induction was associated with a higher rate of CS, probably because it was the preferred method used in group 5.